Design Mapping of Wastewater Treatment Installation (IPAL) in the Coal Special Port Area of PT Telen Orbit Prima Montallat District North Barito Regency Central Kalimantan Province - Firdaus Firdaus; Hendrik Segah; Yetri Ludang (Journal of Social Research, 2023)
This research aims to design an effective Waste Water Treatment Plant (IPAL) system in the special port area of Persia (PT) in order to ensure the sustainability of mining operations while complying with environmental regulations. The IPAL design is based on assessing the topography, hydrological characteristics, and water quality of the catchment area. Water quality analysis is carried out both during the dry season and after rain, taking important parameters such as pH, Total Suspended Solids (TSS), iron (Fe), and manganese (Mn) into consideration. The results of this research provide important information for designing IPALs that comply with environmental conditions and applicable regulations. Based on the data that has been analyzed, it can be concluded that the proposed WWTP design is an effective solution in managing coal mining wastewater in this port area.